The tjoeverian community of Ennerdale: methamphetamine use in the context of concatenated violence. - Bester, Alda Sherlenia (My University, 2022)
This ethnographic study focusses on ‘lolly lounges’ in the community of Ennerdale, south of Johannesburg. A lolly lounge is a social space in which the tjoeverian community of Ennerdale smoke the illegal substance Crystal Methamphetamine (meth) through a glass pipe. The tjoeverian community is a group of drug users, who take Crystal Methamphetamine as well as substances such as Mandrax and dagga. A very small proportion of tjoeverians also inject the meth into their veins. Meth is referred to as food in this space and is considered nourishment for the soul. Ennerdale is based approximately 35 km south of the Johannesburg CBD. This community was considered a Coloured area under the Apartheid regime. It has since received considerable media attention for its usually violent protests linked to issues of state abandonment such as overcrowding, unemployment, housing shortages and the recent establishment of lolly lounges. This thesis is based on interviews with 20 participants (4 lolly lounge owners, 2 patrons from each lolly lounge and 8 community members, two Community Policing Forum members). The research explores the lives and interactions of this group of meth smokers and how they interact with the wider community and the state, in frequently violent encounters. It proposes that lolly lounges must be understood within concatenated networks of interpersonal, collective and state violence.
A research report submitted in partial fulfilment of the requirement for the degree of Master of Arts in Anthropology to the Faculty of Humanities, University of the Witwatersrand, 2022
Keywords: Lolly lounges; Tjoeverian community; Stractural violence; Community policing forum